Epistemology in Islam: The Integration of Science and Religion According to Kuntowijoyo and Its Correlation with the National Law Establishment - Anindya Aryu Inayati; Agung Barok Pratama (Tasfiyah: Jurnal Pemikiran Islam, 2022)
Kuntowijoyo is one of the prominent Indonesian Muslim philosophers who discusses Islamic epistemology. However, unlike most philosophers who focus on the process of Islamization of knowledge, Kuntowijoyo actually formulated the concept of scientific which is an epistemological idea of integrating between Islam and the sciences. The idea of integrating science and religion needs to be re-echoed in the third decade of the 21st century, given that this long-term program has not produced much in the treasures of Islamic scholarship, especially in Indonesia.This study aims to review the idea of integrating science and religion in the work of Islam as Science compiled by Kuntowijoyo. The type of this research is library research with analytical descriptive method. The object of research is the book Islam as a science, by Kuntowijoyo. The results of this study, that Kuntowijoyo offers a process of integrating science and religion in a concept he named scientific Islam, where science is derived from the texts of the Qur'an and As-Sunnah into the context of scientific reality. Kuntowijoyo hopes that, with this idea of scientific Islam, the sciences that are built can stand on the basis of the integration of science and religion, without dominating one of them, so that it can be applied to all humans in general. included in the development of national law because the concept of scientific Islam which initiates the integration between science and religion is also in line with the concept of the formation of national law that integrates religion and the state.